2019
DOI: 10.1177/1179069518824851
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oral Administration of Amantadine on Neurological Outcome of Patients With Diffuse Axonal Injury in ICU

Abstract: Traumatic brain injury is a major cause of death and disability in adults. This study investigated the effect of oral administration of amantadine on the neurological outcomes of patients with diffuse axonal injury (DAI) in the intensive care unit (ICU). This double-blind clinical trial was conducted in the ICU of Imam Hospital in Urmia. Patients with DAI were intubated and received mechanical ventilation in the ICU. They were divided into 2 groups: patients receiving amantadine (A) and placebo (P). The acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…AMA continues to be investigated as a therapeutic agent for improving level of consciousness and functional recovery for persons remaining in states of DoC. 3 6 The seizure risk for rTMS paired with AMA is unknown; theoretically, AMA by itself may lower seizure threshold. A recent systematic review reports a 0.7% prevalence of seizure (2/259 patients) with 100 to 200 mg twice a day of AMA.…”
mentioning
confidence: 99%
“…AMA continues to be investigated as a therapeutic agent for improving level of consciousness and functional recovery for persons remaining in states of DoC. 3 6 The seizure risk for rTMS paired with AMA is unknown; theoretically, AMA by itself may lower seizure threshold. A recent systematic review reports a 0.7% prevalence of seizure (2/259 patients) with 100 to 200 mg twice a day of AMA.…”
mentioning
confidence: 99%
“…10 Two additional smaller randomized controlled trials have investigated the efficacy of amantadine during the acute hospitalization. 19,26 Similar to the landmark clinical trial discussed earlier, Ghalaenovi et al found a higher Glasgow Coma Scale (GCS) score change in patients receiving amantadine (n ¼ 19) versus placebo (n ¼ 21) between day 1 and day 7, suggesting a faster time to recovery. 19 In addition, the authors affirmed previous findings that no difference was observed in long-term functional outcome measures reported at 6 months after a 6-week treatment period, suggesting that while amantadine may accelerate the recovery of arousal, this does not change long-term outcomes.…”
Section: -Hydroxytryptamine Neuronmentioning
confidence: 67%
“…While Ghalaenovi and colleagues evaluated a lower dose of amantadine (100 mg twice daily), Abbasivash et al evaluated a higher amantadine dose (200 mg twice daily) in patients with severe TBI ( n = 33) compared with placebo ( n = 33) that was continued until extubation or recovery to GCS > 8. 26 Patients in this study were followed up only to hospital discharge and improvements in arousal beyond that time were not reported, but no difference was observed in the duration of mechanical ventilation, GCS, or Glasgow Outcome Scale (GOS) scores at hospital discharge (mean hospital length of stay: 29 and 32 days, respectively).…”
Section: Dopaminergic Agents For Neurostimulationmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, in the study by Rahman Abbasivash et al, the effect of oral administration of amantadine on the neurological outcomes of patients with diffuse axonal injury (DAI) in the intensive care unit was evaluated. ( Abbasivash et al, 2019 ) All patients in this study were intubated and received mechanical ventilation. They were divided into 2 groups: patients receiving amantadine and placebo.…”
Section: Discussionmentioning
confidence: 99%